Diabetic cardiomyopathy: merely a complication or a distinct understudied disease? - B. U. Mardanov; M. N. Mamedov (Рациональная фармакотерапия в кардиологии)
Since the 1970s, researchers have investigated a specific disorder of myocardial structure and function in diabetes mellitus (DM) — diabetic cardiomyopathy (DC) – whose primary clinical manifestation is heart failure (HF). Numerous studies demonstrate a high risk of HF in patients with type 2 diabetes mellitus (T2DM), alongside worsened prognosis when these conditions coexist. For instance, the Kaiser Permanente population study demonstrated a 3- to 4-fold higher HF risk in T2DM patients under 75 years compared to non-diabetic individuals. Despite accumulated research, DCM remains classified by many experts as a complication of DM rather than a distinct entity, fueling ongoing discussion. At the same time, ongoing studies increasingly reveal characteristic disorders of heart function with pathophysiological features, suggesting that DCM may constitute a separate condition occurring within the diabetic context. To date, there are no generally accepted clinical guidelines for DCM diagnosis and management, and therefore there is a need for standardized diagnostic criteria to identify high-risk populations. The review analyzes current literature data on terminology, etiology, pathogenesis, and treatment. Systematisation of existing knowledge and clear diagnostic criteria would facilitate greater focus on novel treatment strategies.